The Importance of Context for the Development of Labour Market Theory and Policy - Morris Altman (Journal of Contextual Economics – Schmollers Jahrbuch, 2021)
Labour market theory underlies much of economic analysis with implications for theory and policy. I argue that conventional approaches to the labour market as well as more modern approaches represented by aspects of behavioural labour economics and Keynesian economics are often decontextualized from how individuals actually behave and the institutions affecting their behaviour. Building labour market models with empirically valid assumptions about human behaviour and individuals' decision-making environment casts doubt on key core predictions of contemporary economics, such as: higher wages are bad for the economy; improvements in conditions of work and social support are economically damaging; lower real wages are a prerequisite to increasing macro employment, and workers prefer leisure over work. These models also challenge the view put forth by heuristics and biases type behavioural economists that workers behave irrationally, are biased, and therefore make decisions that are sub-optimal, damaging to themselves and the economy at large.
Keywords: D01; D02; E10; E20; O10; 330; Context; Assumptions; Behavioural Economics; Labour Markets; High Wages; Policy; Wellbeing